KopAL - A mobile orientation system for dementia patients - Fudickar, Sebastian; Schnor, B (Intelligent Interactive Assistance and Mobile Multimedia Computing, 2009)
In the aging sectors of societies in the western world, dementia and its characteristics such as disorientation and obliviousness are becoming a significant problem to an increasing number of people and health systems. In order to enable such dementia patients to regain a self-determined life, we have developed a mobile orientation system with a focus on minimal operational costs and a speech based human computer interface. This system assists dementia patients in everyday problems, such as remembering appointments and staying on track within their familiar surroundings as well as informing caretakers in critical situations.